1975
DOI: 10.1071/ea9750239
|View full text |Cite
|
Sign up to set email alerts
|

A study of phosphorus nutrition and water supply on the early growth and survival of buffel grass grown on a sandy red earth from south-west Queensland

Abstract: The influence of phosphorus application on the growth and drought survival of buffel grass on a sandy red earth in south west Queensland was studied in a series of pot experiments. An omission nutrient trial showed phosphorus was the principal nutrient limiting seedling growth, the severity of the deficiency increasing with time. A further pot experiment showed that at rates greater than 24 kg P ha-1 luxury consumption occurred. The critical phosphorus concentration for the plant was estimated to be 0.26 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…This analysis results indicated that the clay soil test had adequate nutrient content and imposed no chemical limitations for buffel grass germination (Christine, 1975).…”
Section: Methodsmentioning
confidence: 98%
“…This analysis results indicated that the clay soil test had adequate nutrient content and imposed no chemical limitations for buffel grass germination (Christine, 1975).…”
Section: Methodsmentioning
confidence: 98%
“…In Tunisia, several authors mention the species is scarce and growth is stunted, because it is selectively overgrazed (Waechter, 1982;Ferchichi et al, 1991;ChamK eb et al, 1992), and because its typical 'flush growth', as a C -photosynthesizer in an arid Mediterranean environment, occurs when other grazing resources are scarce. Alternatively, C. ciliaris would need high available-phosphorus levels (Christie, 1975) so that continued soil exhaustion could have interacted with overgrazing to cause its decline. Cenchrus ciliaris can only complete a phenological cycle when high temperature is combined with adequate soil moisture.…”
Section: Cenchrus Ciliaris In North Africamentioning
confidence: 97%
“…In Australia, evidence of nutrient limitations has been largely derived from pot experiments that are difficult to extrapolate to field conditions. For example, field responses of grasses to added P were either negligible (Friedel et al, 1980) or were not tested (Christie, 1975;Silcock et al, 1976), while growth in the glasshouse was increased with added P. Moreover, some pot trials were confounded by the addition of basal nutrients (e.g. N, K, trace) in combination with different rates of P (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…N, K, trace) in combination with different rates of P (e.g. Christie, 1975;McIvor, 1984;Armstrong & Helyar, 1993).…”
Section: Introductionmentioning
confidence: 99%